Noxious chemical discrimination by Tribolium castaneum TRPA1 channel in the HEK293 cell expression system - Kenji Shimomura; Hinoki Oikawa; Kosuke Yamamoto; Takehito Terajima; Shunsuke Yajima; Motohiro Tomizawa (Current Research in Insect Science, 2023)
Nociception is the sensory perception of noxious chemical stimuli. Repellent behavior to avoid noxious stimuli is indispensable for survival, and this mechanism has been evolutionarily conserved across a wide range of species, from mammals to insects. The transient receptor potential ankyrin 1 (TRPA1) channel is one of the most conserved noxious chemical sensors. Here, we describe the heterologous stable expression of Tribolium castaneum TRPA1 (TcTRPA1) in human embryonic kidney (HEK293) cells. The intracellular Ca2+ influx was measured when two compounds, citronellal and l-menthol, derived from plant essential oils, were applied in vitro using a fluorescence assay. The analysis revealed that citronellal evoked Ca2+ influx dose-dependently for TcTRPA1, whereas l-menthol did not. In combination with our present and previous results of the avoidance-behavioral assay at the organism level, we suggest that TcTRPA1 discriminates between these two toxic compounds, and diversification in the chemical nociception selectivity has occurred in TRPA1 channel among insect taxa.